Comparative study of testing the efficacy of turnip extract water vs. warm salt bath in the symptomatic relief of chill blains - Sultan, Nadia; Butt, Ghazala; Omer, Saira; Rehman, Saima; Chaudhry, Asad Ali (Journal of Pakistan Association of Dermatologists, 2020)
Background Chill blains is a clinical presentation of vasoconstriction of small vessels of the extremities due to repeated exposure to extreme cold, resulting in painful toes , fingers, ear , nose and heels along with tenderness, erythema and blister formation. Turnips have long been used in ancient time and in the era of ayurvedic for curing multiple skin diseases as they have been known to be rich in nutrients particularly vitamin C and nitrates which act as vasodilators.1 Turnips are rich in potassium, which help to eliminate sodium from the body which in turn causes vasodilation. Objective To compare the efficacy of warm turnip extract water versus warm salt water soaks in the symptomatic relief of chill blains, over the course of three weeks, while using topical anti inflammatory medications. Methods This study was conducted over a period of four months starting from November 2018 till February 2019 at the outpatient of dermatology department at Punjab Rangers Teaching Hospital, Lahore. A total number of 70 patients who presented to the skin OPD with chill blains were enrolled in the study and were divided into two equal groups. One group was taken as cases (35) & the other as controls (35). Cases were labeled Group A & controls were labeled Group B. The cases were advised to soak their feet in turnip extract water for fifteen minutes daily before bedtime, while the other group were taken as controls & advised daily warm saline soaks at night with 8 tablespoon of salt in 4 liters of warm water. To prepare the turnip extract, 1 kilogram of turnips were allowed to boil in approximately 4 liters of water until they were soft enough to mash and the water turned brown. Then the water was allowed to cool to a tolerable temperature. After soaking their feet for fifteen minutes in either water, both groups were advised to dry them with a piece of clean towel & then apply topical mixed anti-inflammatory creams. Patients were instructed to repeat these daily soaks along with the topical steroid preparation for three weeks and then followed up in the OPD after this time to compare the effectiveness of each. The variables that were assessed on the first follow up visit were pain, pruritus, erythema & edema. Results Both Group A & Group B , cases and controls were observed for the response regarding the efficacy of turnip extract water versus saline soaks on the first follow up after three weeks. There was a very significant response among the case group compared to a variable response among the controls. Conclusion Based on the results of current study, it can be concluded that the ayurvedic remedy of using warm turnip extract water does contribute towards improving the efficacy of topical steroid preparation in comparison to the home remedy of saline soaks use with the same steroid anti-inflammatory preparation, in improving the pain, erythema, swelling & pruritus of chill blains.